The history of Phoenicia - Elayi, Josette (Lockwood Press, 2018)
"The history of the Phoenicians, explorers and merchants, is little known. What a paradox for this ingenious people, who invented the alphabet, to have left so few written traces of their existence. Their literature, recorded on papyrus, has disappeared. And yet this civilization fired the imagination of its contemporaries--the Jews in particular--inspiring terror among the Romans and Greeks, who depicted them as a cruel people who practiced human sacrifice. Their clients were the pharaohs and the Assyrians, their ships criss-crossed the Mediterranean, laden with the luxuries of the day such as wine, oil, grain, and mineral ore. Buried beneath the modern cities of Lebanon, and a few of Syria and Israel, ancient Phoenicia has resuscitated in this volume."--Publisher's description